Sacredness of food offerings for spirits in the spiritual healing practices of the Bajau Laut ethnic - Amsalib Pisali; Ratna Fazlinda Jelly; Sharifuddin Zainal; Mohd Kipli Abdul Rahman; Mashor Awang Long; Adinda Usin Muka (AMER ABRA cE-Baby e-International Publishing House, Ltd, 2025)
This study explores the role of food offerings in Bajau Laut's spiritual healing rituals as a medium of sacred communication. These offerings are rooted in transcendental connections with ancestral spirits and symbolize beliefs, values, and religious systems passed down through generations. Using Peirce's semiotic framework, the study classifies food as icons, indexes, and symbols, each carrying distinct meanings. Employing a qualitative, phenomenological approach, data is gathered through participatory observation and interviews. Findings reveal that sacred communication in these rituals is a dynamic interpretative process, highlighting food's role in spiritual-human interaction and contributing to the discourse on semiotics and food anthropology.